2017
DOI: 10.1038/nature21723
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics on any population structure

Abstract: Evolution occurs in populations of reproducing individuals. The structure of a population can affect which traits evolve. Understanding evolutionary game dynamics in structured populations remains difficult. Mathematical results are known for special structures in which all individuals have the same number of neighbours. The general case, in which the number of neighbours can vary, has remained open. For arbitrary selection intensity, the problem is in a computational complexity class that suggests there is no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
483
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 424 publications
(503 citation statements)
references
References 65 publications
17
483
2
1
Order By: Relevance
“…Social interactions, which are typically multilateral (50) and nonlinear (51,52), cannot be expressed by a single benefit and cost. Complex population structures (43,46,53,54) cannot be captured by a single relatedness quantity. Assortment among relatives often has a positive effect on cooperation (41,(44)(45)(46)(47), but in other cases it has a negative effect (48,55) or no effect at all (42,45).…”
Section: Discussionmentioning
confidence: 99%
“…Social interactions, which are typically multilateral (50) and nonlinear (51,52), cannot be expressed by a single benefit and cost. Complex population structures (43,46,53,54) cannot be captured by a single relatedness quantity. Assortment among relatives often has a positive effect on cooperation (41,(44)(45)(46)(47), but in other cases it has a negative effect (48,55) or no effect at all (42,45).…”
Section: Discussionmentioning
confidence: 99%
“…Our generalized, axiomatic definition of information enables this framework to be applied to a variety of physical, biological, social, and economic systems. In particular, we envision applications to spin systems [1,17,83,84], gene regulatory systems [85][86][87][88][89][90][91], neural systems [92][93][94], biological swarming [95][96][97], spatial evolutionary dynamics [82,98,99], and financial markets [22,59,81,[100][101][102][103][104][105].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Understanding evolution and ecology in such spatially extended systems is a challenging and long-studied problem [2933]. Recent studies have demonstrated rich dynamics when inter-cellular interactions are defined on heterogeneous complex networks [3436], where spatial structure can (for example) promote invasive strategies in tumor models [35] or modulate fixation times on random landscapes [34]. Remarkably, in the weak selection limit, evolutionary dynamics can be solved for any population structure [36], providing extensive insight into game-theoretic outcomes on complex networks.…”
mentioning
confidence: 99%